Research analyse of potential circadian aspects in boxing - Krejci, M.; Harada, T.; Kawamata, M. (Slovak Journal of Sport Science, 2018)
There are given in the presented paper outputs of five years long term basic research of the circadian determinants influence on athlete's performance in the framework of the Czech - Japan joint project W/VSP/161/I. In the paper we present the focus on circadian determinants, which can be important for performance in sport discipline boxing, e.g. on the circadian preferences and habits of boxers in Czech Republic. The main objective of the investigation was to analyse circadian preferences and habits of boxers in context of professional/amateur boxing. The partial goal was to analyse differences between professional and amateur performance of male boxers. In total 91 Czech boxers (37 professional boxers, 54 amateur boxers), in age interval 21- 35 year old, median 26.2 years old, participated in the investigation procedure. The diagnostic method Questionnaire of Circadian Typology "CIT" for adults (Harada, Krejcí - Czech version, 2010) was used. The statistical methods included One-way non-parametric ANOVA SPSS, with using Fisher Exact Test and Mann-Whitney U test. Results demonstrate from the view of chronotype that professional boxers are more evening typed than amateur boxers. Significant differences in the marker "Difficulty fall asleep" were found between professional and amateur boxers. Spent time in night in front of blue light in monitors and displays negatively influenced quality of sleep. Professional boxers tend to adhere to regular eating habits in comparison with amateur boxers. In professional boxers were analysed higher levels of psychological stability and self-control than in amateur boxers. Conclusions presented in the paper can serve background material, for example, to set up an appropriate intervention program for boxers, whether professional or amateur boxers. Especially is advisable to recommend to boxers to avoid blue light sources in the night before falling asleep, because guides to prolong the sleep cycle and reduce the quality of sleep.